Comprehensive analysis of cryptocurrency, virtual digital assets, and distributed ledger technology with insights into Indian policies and research trends - Kaushik Ghosh; Prabir Kumar Das (Discover Analytics)
Abstract This study offers a detailed literature review and bibliometric analysis of cryptocurrency, virtual digital assets (VDA), and distributed ledger technology (DLT)-based digital currencies. We analyze current research and publishing trends, particularly in forecasting cryptocurrency price volatility. The paper categorizes the development and maturity of various analytic methods employed across domains like centralized finance, decentralized finance, and blockchain. The review highlights both traditional econometric models and emerging machine learning algorithms in these areas, illustrating their evolution and application depth in the literature. Our research further explores national policies on VDA and DLT, focusing on India. We employ sentiment analysis to assess the tone and implications of Indian legislation, policies, and court orders concerning VDA. The analysis reveals a predominantly neutral stance, with a notable positive tilt, suggesting a favorable sentiment from Indian authorities towards these emerging technologies. The sentiment distribution also shows that the Indian authorities are anticipatory and expressing trust in their policies and regulations. Although policy frameworks are still evolving, efforts show a drive towards creating a safe, inclusive environment for VDA and DLT applications in India. Finally, we identify existing research gaps, propose theoretical questions, and recommend potential directions for national-level policies based on our findings.